Surprise house - Brown, Abbie Farwell, 1871-1927; Grose, Helen Mason, 1880-1971 (Salt Lake City, UT : Project Gutenberg, 2022)
"Surprise House" by Abbie Farwell Brown is a children$1 (Bs novel written in the early 20th century. The story centers around the Corliss family, who inherit an old house from their eccentric Great-Aunt Nan Corliss. Upon exploring their new home in Crowfield, they discover an array of peculiar curiosities and hidden surprises that reflect Aunt Nan's whimsical personality, suggesting that the house itself is full of secrets waiting to be uncovered. The opening of "Surprise House" introduces the Corliss family as they arrive at the old, charming home that has been neglected and abandoned since Aunt Nan's passing. Dr. Corliss, his wife, and their two children, Mary and John, explore the house and encounter various oddities, hinting at Aunt Nan's penchant for mischief. The family begins to piece together Aunt Nan's legacy, encountering practical jokes and unexpected discoveries, like a library specifically designated for Mary. The stage is set for a story filled with mystery, humor, and the family$1 (Bs growing fondness for their quirky relatives and old home, inviting readers to share in their adventures and the surprises that lie ahead. (This is an automatically generated summary.)s
Chapters of this book appeared as a serial in The Young Churchman, under the title "Aunt Nan's legacy." cf. Note.
Release date is 2022-12-11
David E. Brown and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Cats -- Juvenile fiction; Inheritance and succession -- Juvenile fiction; Mystery fiction; Families -- Juvenile fiction